Fully CMOS Boost Converter Operating at 2.65 GHz for Photovoltaic Energy Harvesting - Pedro Mendonca Dos Santos; Ricardo Alexandre Marques Lameirinhas; Catarina P. Correia V. Bernardo; Joao Paulo Neto Torres; Antonio Serralheiro; Rafael Vieira; Nuno Lourenco (IEEE Access)
This research describes the design of a fully CMOS-integrated boost DC-DC converter to be supplied by an ultra-low power solar cell for energy harvesting applications. The monolithic system is based on the inductive boost converter, with both the energy storage spiral inductor and the output filter capacitor integrated together with an LC oscillator at 2.65 GHz, to drive both MOSFET switches, in a 110 nm CMOS process. The system delivers 1.2 V for a 10 k $Ω $ load, with an output power of the order of $144~μ $ W. Experimental results also show that the proposed inductor-based fully CMOS DC-DC boost converter has a record low silicon footprint (0.13 mm2) and highest power density (1.1 mW/mm2) when compared with other counterparts resorting to the same boost topology. The fully integrated solution can be used in the power management units of stand-alone or remote integrated systems, for several applications such as biomedical or IoT, usually characterised for ultra-low voltage photovoltaic applications.